Perceptions of infection control practices among health professionals - Watkins, Rochelle; Wynaden, Dianne; Hart, Linda; Landsborough, Ian; McGowan, Sunita; Speed, G.; Orb, Angelica; Henderson, Saraswathy; Wilson, S.; Calnan, W. (eContent Management Pty Ltd, 2006)
Infection control practice is a cornerstone of modern health care. However, there is minimal research into health professionals' perception of infection control practices and how those perceptions influence staff compliance with recommended protocols. The objective of this study was to explore health care professionals' perceptions of infection control practices in relation to the management of infectious diseases. A grounded theory approach was used as the research framework. Semi-structured interviews were completed with a sample of 16 nurses and doctors working at hospitals in Western Australia. Four major categories emerged from the data. These were: knowledge, culture, conflict, and risk assessment. The findings indicate the importance of both individual and organisational factors in determining clinicians' levels of compliance with recommended infection control practices. Identification of the factors that influence health professionals' level of compliance can be used to develop strategies to support long-term compliance with infection control practices.